(untitled) (Eurasian Journal of Ecology, 2019)
Abstract. In the article has been shown results of the monitoring the territory of the former storehouse pesticides (vil. Kyzyl-Kairat, Talgar district, Almaty region) and assessing the remediation ability soil contaminated with POPs (persistent organic pesticides) of the new bioenergetic species Miscanthus sinensis. Established that the soil around the former warehouses contaminated with persistent organic pesticides (HCB, α-HCH, γ-HCH, β-HCH, δ-HCH, DDT, 4.4’DDE, 2.4’DDD, 4.4’DDD, aldrin, heptachlor, hexabromobenzene, heptachloroepoxide, deldrin, dibutylendan, keltan, methoxychlor, endrin, endrin aldehyde, endosulfan sulfate, endosulfan, chlordane, chlorobenzylate), the concentrations of which exceeded MAC up to 120 times. The main soil contaminants were pesticides – α-HCH, β-HCH, δ-HCH, DDT, 4.4’DDE, 2.4’DDD, aldrin, deldrin, endrin, heptachloroepoxide, endosulfan 1 and chlorobenzylate. M. sinensis was grown on the contaminated soil with pesticides was found that the plant has tolerance (tolerance index 0.76) and the ability to extract up to 11 μg of DDT metabolites from contaminated soil. Revealed a decrease in the content of chlorophyll a and an increase of auxiliary pigments – chlorophyll b and carotenoids in the leaves, as the adaptive reaction of the photosynthetic apparatus to the action of a xenobiotic. The results obtained indicate on the adaptability of M. sinensis to high concentrations of POPs pesticides in the soil and the prospect of their use for the development of phytoremediation technology. Key words: POPs pesticides, plant, productivity, photosynthesis, phytoremediation, soil